Infection Prevention and Control in the Emergency Department Unit in King Khalid Hospital, Hail City, Saudi Arabia - Jammilah AlAnazy; Wessam Mwandenga (Evidence-Based Nursing Research)
Context: The emergency department presents unique challenges to infection control and prevention. Infection control (IC) activities include the identification of infectious disease processes, surveillance, and epidemiologic investigation, preventing/controlling the transmission of infectious agents/healthcare-associated infections, employee/occupational health, management and communication, education and research, managing the environment of care, and cleaning, sterilization, disinfection, and asepsis.